An Assessment of Almajiri Integrated Model School Pupils' Performance in Qur'anic Subjects in Sokoto State, Nigeria - Abdulhameed Ishola Jimba (International Journal of Islamic Educational Psychology, 2021)
Almajiri is an education system practiced in northern Nigeria whereby Almajiri pupils are only exposed to Quranic learning. For these pupils to become relevant and valuable in this modern society, the Federal Government of Nigeria formulated a formalizing their Almajiri education system and integrated Western education without jeopardizing Quranic learning. To find out if Almajiri education is not being negatively affected because of the policy, this study assessed Almajiri Integrated School Pupils' performance in Quranic subjects in Sokoto State, Nigeria. The research method employed was a descriptive survey. Using the purposive sampling technique, four schools (2 urban and 2 rural schools) where the needed data were readily available were sampled. Two hundred seventy-three (273) subjects (94 from urban and 179 from rural areas) were purposively tested for the study. Pro-forma was designed as a research instrument and collected the 2013/2014 primary 3 Promotional Examination Results. The Percentage, Mean and Standard deviation, Bar Chart, and t-test statistical tools were used for data analysis. The study revealed, among others, that the general performance of Almajiri Integrated Model School pupils in the Qur'anic subjects was below average. The paper concluded an urgent need to empirically explore factors responsible for the low performance to improve it.